2001
DOI: 10.1002/j.2161-007x.2001.tb00204.x
|View full text |Cite
|
Sign up to set email alerts
|

Toward Forgiveness: The Role of Shame, Guilt Anger, and Empathy

Abstract: This research explored forgiving and its relationship to adaptive moral emotional processes: proneness to shame, guilt, anger, and empathic responsiveness. Gender differences associated with forgiving were analyzed. Participants were 138 graduate students in a large northeastern urban university. Results revealed that guilt‐proneness was positively related to Total Forgiveness, as were Empathetic Concern and Perspective Taking. A positive relationship between anger reduction and Overall Forgiveness was found. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
65
1
7

Year Published

2003
2003
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 91 publications
(77 citation statements)
references
References 29 publications
4
65
1
7
Order By: Relevance
“…Fincham et al (2002) showed a link between forgiveness and emotional empathy in a hypothetical marital offense. Konstam, Chernoff, and Deveney (2001) showed relationships between forgiveness and both cognitive and emotional empathy. Macaskill, Maltby, and Day (2002) reported a relationship between empathy and forgiveness of others but not oneself.…”
Section: Empathy and Forgivenessmentioning
confidence: 98%
“…Fincham et al (2002) showed a link between forgiveness and emotional empathy in a hypothetical marital offense. Konstam, Chernoff, and Deveney (2001) showed relationships between forgiveness and both cognitive and emotional empathy. Macaskill, Maltby, and Day (2002) reported a relationship between empathy and forgiveness of others but not oneself.…”
Section: Empathy and Forgivenessmentioning
confidence: 98%
“…Research on forgiveness is growing rapidly, including the roles played by situational factors (McCullough, Fincham, & Tsang, 2003;Takaku, 2001), intrapersonal factors and individual differences (Bradfield & Aquino, 1999;Brown, 2003;Konstam, Chernoff, & Deveney, 2001) and dyadic relational factors (Fincham & Beach, 2002;Finkel, Rusbult, Kumashiro, & Hannon, 2002;Friesen et al, 2005). However, as mentioned earlier, there has been relatively little interest in a possible consensual lay representation of forgiveness, and only a handful of studies have examined forgiveness from a lay perspective.…”
Section: Lay Perspectives Of Forgivenessmentioning
confidence: 99%
“…Affetme bireyin kendisi, başkaları ve dünya ile ilgili görüşlerini yeniden ele alıp, bunları tutarlılıkla bütünleştirerek kişisel bir dönüşüme yönelme sürecidir (Doyle, 1999;Thompson ve diğ., 2005). Affetmek belirli bir zaman geçince oluşur ve bir seçim yapmayı içerir (Kontsam, Chernoff ve Deveney, 2001). İçsel affetme suçlunun yaptıklarını gözden geçirme ve buna karşın yeniden bir bilişsel yapılanmayı gerektirirken, kişilerarası affetmede yapılanlara rağmen ilişkinin devamı söz konusudur (Exline ve Baumeister, 2000;Gordon, Baucom ve Snyder, 2000).…”
Section: Introductionunclassified